Vibrational and vibrational-torsional interactions in the 0–600 cm-1 region of the S1 ← S0 spectrum of p-xylene investigated with resonance-enhanced multiphoton ionization (REMPI) and zero-kinetic-energy (ZEKE) spectroscopy - Tuttle, William D.; Gardner, Adrian M.; O'Regan, Kieran B.; Malewicz, William; Wright, Timothy G. (American Institute of Physics Publishing, 2017)
We assign the 0–600 cm-1 region of the S1 ← S0 transition in p-xylene using resonance-enhanced multiphoton ionization (REMPI) and zero-kinetic-energy (ZEKE) spectroscopy. In the 0–300 cm-1 range, as well as the intense origin band there are a number of torsional and vibration-torsion (vibtor) features. The latter are discussed in more detail in an accompanying paper [Gardner et al. J. Chem. Phys. XXX, xxxxxx (2016)]. Here we focus on the origin and the 300–650 cm-1 region, where vibrational bands and some vibtor activity is observed. From the origin ZEKE spectrum we derive the ionization energy of p-xylene as 68200 ± 5 cm-1. The assignment of the REMPI spectrum is based on the activity observed in the ZEKE spectra coupled with knowledge of the vibrational wavenumbers obtained from quantum chemical calculations. We assign several isolated vibrations, and a complex Fermi resonance that is found to comprise contributions from both vibrations and vibtor levels, and we examine this via a two-dimensional ZEKE (2D-ZEKE) spectrum. A number of the vibrational features in the REMPI and ZEKE spectra of p-xylene that have been reported previously are reassigned and now largely consist of totally-symmetric contributions. We briefly discuss the appearance of non-Franck-Condon allowed transitions. Finally, we find remarkably similar spectral activity to that in the related disubstituted benzenes, para-difluorobenzene and para-fluorotoluene.